Study of suprathermal electron dynamics during electron cyclotron current drive using hard x-ray measurements in the TCV tokamak. (29th September 2020) - Choi, D; Coda, S; Decker, J; Cazabonne, J A; Peysson, Y
Abstract: Suprathermal electron dynamics in real and momentum spaces plays an important role in the physics of electron cyclotron current drive (ECCD), in particular for predicting the wave driven current. In the TCV tokamak, a hard x-ray spectroscopy system equipped with digital pulse detection enables detailed studies of the creation and relaxation of suprathermal electrons. The time evolution of hard x-ray spatial profiles and energy spectra is observed utilizing a minimally perturbative ECCD modulation technique. Time-dependent Fokker-Planck modeling combined with a hard x-ray synthetic diagnostic is used to interpret experimental results and test various suprathermal electron transport models. The comparison suggests a dependency of the radial transport on the EC wave power.